Impact of Internal Migration and Socioeconomic Consequences (A Case of Bharatpur Metropolitan ward no 11) - Chalise, Ambika (Journal of Balkumari College, 2024)
The study explores the socio-economic impacts of migration in Bharatpur Metropolitan-11, focusing on changes in occupation, landholding patterns, and socio-cultural life. It found that migration initially started as temporary but became permanent as basic facilities were established. Primary drivers include economic opportunities, education, and improved living conditions. However, challenges like inadequate water supply and environmental pollution persist. The study recommends improving agricultural productivity, enhancing infrastructure, and ensuring equitable access to essential services for sustainable migration integration.